The New Antimicrobial Peptide SpHyastatin from the Mud Crab Scylla paramamosain with Multiple Antimicrobial Mechanisms and High Effect on Bacterial Infection - Shan, Zhongguo; Zhu, Kexin; Peng, Hui; Chen, Bei; Liu, Jie; Chen, Fangyi; Ma, Xiaowan; Wang, Shuping; Qiao, Kun; Wang, Kejian (Frontiers in Microbiology, 2016)
SpHyastatin was first identified as a new cationic antimicrobial peptide (AMP) in hemocytes of the mud crab Scylla paramamosain. Based on the amino acid sequences deduced, it was predicted that this peptide was composed of two different functional domains, a proline-rich domain (PRD) and a cysteine-rich domain (CRD). The recombinant product of SpHyastatin displayed potent antimicrobial activities against the human pathogen Staphylococcus aureus and the aquatic animal pathogens Aeromonas hydrophila and Pseudomonas fluorescens. Compared with the CRD of SpHyastatin, the PRD presented better antimicrobial and chitin binding activities, but both regions were essential for allowing SpHyastatin complete antimicrobial activity. The binding properties of SpHyastatin to different microbial surface molecules suggested that this might be an initial and crucial step for performing its antimicrobial activities. Evaluated using propidium iodide uptake assays and scanning electron microscopy images, the antimicrobial mechanism of SpHyastatin was found to be prone to disrupt cell membrane integrity. Interestingly, SpHyastatin exerted its role specifically on the surface of S. aureus and Pichia pastoris whereas it directly killed P. fluorescens through simultaneous targeting the membrane and the cytoplasm, indicating that SpHyastatin could use different antimicrobial mechanisms to kill different species of microbes. As expected, the recombinant SpHyastatin increased the survival rate of crabs challenged with Vibrio parahaemolyticus. In addition, SpHyastatin could modulate some V. parahaemolyticus-responsive genes in S. paramamosain.